La insoportable burocratización del internet. La propuesta de OSIPTEL para regular la “neutralidad de red” en el Perú - Zúñiga Palomino, Mario (Pontificia Universidad Católica del Perú, 2015)
This article analyzes the reasons for the so-called “network neutrality” and its regulation in Peru (including the laws regulating as a proffer recently presented by OSIPTEL); consisting primarily of equal treatment of all traffic, content or application by internet service providers. From Economic Analysis of Law’sperspective, it has been concluded that the Internet access does not present market failures that justify regulating the conditions of service provision. The author explains why network neutrality may have negative consequences for the internet access market in Peru.

El presente artículo analiza las justificaciones de la denominada “neutralidad de red” y su regulación en el Perú (incluyendo tanto las leyes vigentes como una propuesta de regulación recientemente presentada por OSIPTEL); consistente principalmente en el tratamiento igualitario de todo tráfico contenido o aplicación por parte de los proveedores del servicio de internet. Desde la perspectiva del Análisis Económico del Derecho, se ha concluido que el mercado de acceso a internet no presenta fallas de mercado tales que justifiquen regular las condiciones de prestación del servicio. Asimismo, el autor explica por qué la neutralidad de red puede tener consecuencias negativas para el mercado de acceso a internet en el Perú.
The unbearable bureaucratization of the Internet: The OSIPTEL’s proffer to regulate the “neutrality of red” in Peru
Keywords: Regulation; Internet; Network Neutrality; Free Competition; Osiptel; Market Failures; Regulación; Internet; Neutralidad de Red; Libre Competencia; Osiptel; Fallas de Mercado; https://purl.org/pe-repo/ocde/ford#5.05.00